Afinal, por que os homens não querem as mulheres com esse tal de roque enrow?: uma análise sobre as relações de gênero no rock ‘n’ roll - Cunha, Jessica Rodrigues Araujo (2019)
The work presented here has as a proposal to analyze and discuss how the space of music, more specifically rock ‘n’ roll gets the women involved with the style. Gender relations within this environment appear as an essential factor to understand why even over 80 years, rock remains a mostly masculine space. During the accomplishment of the work a problematic emerges as one of the factors that lead to this exclusion, the relationship of the public and private. The woman, when starts to occupy a space with regard to the public, here in the music, is regarded as an intruder, this is because "naturally" her space is the domestic, in this way, when it is part of any space that escapes its natural, it will be faced with mistrust and suffer with harassment, discourstimulating comments, questioning that aim to test and cause insecurity. The analyses were performed at a first moment by a more general perspective, through readings and discussions about public life of women artists who are already inserted in rock 'n' roll. The following was elaborated an investigation on the role of gender in the production of artists men and women. The research then follows with the interviews conducted with four women from the city of Santa Maria – RS, that somehow are involved with the music and tell me their experiences and trajectory in this way. The final part reserves a conclusion on the experiences reported, together with what was discussed in the previous chapters. The conclusion reveals that even if there is a system to exclude women from public life, these same women are looking for ways to resist, from the creation of new spaces, whose main objective is to be an environment free of male judgments that could be an impediment to them. In addition, the study points to the importance of representativeness for women.